PERAN GURU DALAM MENDORONG SEMANGAT BELAJAR MATEMATIKA SISWA KELAS IV DENGAN MINIMNYA FASILITAS DIGITAL SD NEGERI 2 JEJAWI - Karolin, Indah; Disurya, Ramanata; Tanzimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of teachers in encouraging the mathematics learning motivation of fourth-grade students at SD Negeri 2 Jejawi, where digital facilities are limited. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that teachers play roles as educators, facilitators, guides, and motivators. Teachers utilized simple learning media such as sticks, straws, cardboard, and books to support the learning process. The challenges encountered included differences in students’ abilities, lack of learning focus, limited learning media, and restricted instructional time. To address these challenges, teachers provided repeated explanations, additional exercises, and individual guidance. The study concludes that teachers play a crucial role in enhancing students’ enthusiasm forlearning mathematics despite limited digital facilities.